Strategies to Face the Challenges of the Digital Era Developer Gap at SMAN 5 Kota Tanjung Pinang - Rudi Herdiawan; Panca Ari Pamungkas; Muhamad kurnia Bintan; Ibnu Agus Irawan; Satriadi Satriadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to formulate strategies in facing the challenges of the digital era development gap at SMAN 5 Tanjungpinang City. The digital era has brought significant changes in the world of education, requiring schools to adapt to rapidly developing information and communication technology. SMAN 5 Tanjungpinang has taken strategic steps such as implementing a Learning Management System (LMS), providing fast and stable internet facilities, and developing technology-based learning methods to support effective teaching and learning processes. In addition, the school optimizes quality educators who are experts in the field of information technology to ensure that students receive education that is relevant to the needs of the 21st century., SMAN 5 Tanjungpinang strives to create a learning environment that supports digital transformation holistically, in line with the school's vision to become a creative, innovative, and independent institution. This study concludes that adaptation to the digital era requires synergy between technological infrastructure.